THE MAINTENANCE OF IMPLICATURES IN THE ENGLISH TRANSLATION OF DIALOGUES IN THE NOVEL â€œTHE LAND OF FIVE TOWERSâ€ (A Descriptive Qualitative Study) (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
This final project is about the implicatures found in the source novel entitled â€œNegeri Lima Menaraâ€ written by Ahmad Fuadi that are translated into English by Angie Kilbane entitled â€œThe Land of Five Towersâ€. In understanding the novel, implicature seems harder to be understood since implicature means something beyond what is stated; it may emerge many interpretations. Besides, the implicatures in this novel actually contain the point or message of the novel. So, it is essentially needed for the readers to understand those implicatures for understanding the novel. The objectives of this project are to describe the maintenance of implicatures in the English translation of dialogues in the novel â€œThe Land of Five Towersâ€ and to explain the achievement of the equivalence in meaning. This project was designed as descriptive qualitative. It means that descriptive interpretation was used for examining the data on this research so that the conclusions were based on that interpretation. The object of this project is the utterances containing implicatures that were found in both the Indonesian text as the source text and English text as its translation. Documentation method was used to collect the data in this research. The data was in the form of printed text in the novel, both Indonesian and English versions. In analyzing the data, observation method was done in six steps; they were listing, identifying, classifying, tabulating, interpreting, and drawing conclusion. The findings of this project are from 780 utterances that are stated in these novels, 40 of them are found as utterances containing implicatures. Those utterances flout one of the maxims that Grice stated, whether it flouts maxim of quality, quantity, relevance, or manner. The percentages of them are as follows: there are 11 (27.5%) utterances flouting maxim of quality, 7 (17.5%) utterances flouting maxim of quantity. In addition, there are 6 (15%) utterances flouting maxim of relevance and 16 (40%) utterances flouting maxim of manner. Moreover, for keep maintaining the implicatures, they are mostly translated literally and the translator keeps using some cultural and religious terminologies for keep showing the cultural and religious situation in the translated novel. Furthermore, the meaning equivalence is mostly achieved since the original and the translated novels have the same meaning of the implicatures. By considering them, it can be concluded that the implicatures are mostly maintained when they are translated into English because the meanings and conditions of those implicatures can be similarly understood like what are stated in the ST.